The Economic Impact of the Community There is Religious Tourism to the Tomb of KH Abdul Hamid - Hilmatul I'zzah (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2022)
The economic impact in the form of income is one of the important needs for the community. Income can be used to continue living to meet needs. Tourism activities are one example of activities that can provide an economic impact in the form of income for the surrounding community. An example of a place used in tourism activities is the Religious Tour of the Tomb of KH Abdul Hamid in Pasuruan City. Religious tourism to the grave of KH Abdul Hamid is a favorite tour with many visitors. This study aims to find out the economic impact of the existence of religious tourism on the Tomb of KH Abdul Hamid in Pasuruan City. This study uses a qualitative approach. The data used is primary data with data collection techniques by interview, observation and document study. The sampling technique used was purposive sampling technique. The results of this study indicate that: (1) Religious tourism to the KH Abdul Hamid Tomb has an economic impact on the surrounding community, (2) opens employment opportunities and reduces unemployment and, (3) religious tourism to the KH Abdul Hamid grave can be used as a promotion in introducing Pasuruan City.